2013
DOI: 10.4067/s0034-98872013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Alteración del desarrollo psicomotor en hijos de mujeres con depresión posparto de la ciudad de Valdivia-Chile

Abstract: Background: Postpartum depression (PPD) has adverse effects on psychomotor 07-3.68). This probability was significantly higher among single mothers or those with an unstable partner. Conclusions: PPD has a detrimental impact on psychomotor development of children. (Rev Med Chile 2013; 141: 464-470).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
2
0
4
Order By: Relevance
“…These are in line with those reported by Podestá et al In Chile, who found that once corrected for other variables that affect child development, PPD manifests itself as a very important risk factor 33 .…”
Section: Discussionsupporting
confidence: 92%
“…These are in line with those reported by Podestá et al In Chile, who found that once corrected for other variables that affect child development, PPD manifests itself as a very important risk factor 33 .…”
Section: Discussionsupporting
confidence: 92%
“…Doscientos veintisiete de 493 neonatos no presentaron enfermedad, 109 no contaron con registro y 157 la presentaron siendo en orden, las más frecuentemente observadas, hiperbilirrubinemia neonatal (60), distrés respiratorio transitorio (27), membrana hialina (21) y apnea (16).…”
Section: Resultsunclassified
“…En nuestro país existe un estudio realizado en la Ciudad de Valdivia que demostró que los hijos de madres con DPP tenían el doble de riesgo de déficit en el desarrollo psicomotor a la edad de 18 meses. En este mismo trabajo se encontró una asociación entre la presencia de DPP y un mayor puntaje en el score de riesgo de muerte por neumonía (score de IRA) utilizado en APS 16 .…”
unclassified
“…El impacto de la DPP sobre la salud de los niños es proporcional a la severidad y duración del episodio depresivo, y se agrava en escenarios de adversidad personal y/o social, independiente de las características de los niños 16 . El tratamiento oportuno de esta enfermedad conduce a la mejoría de síntomas y calidad de vida de las madres, y también de los problemas psicoemocionales y conductuales desarrollados por sus hijos 11,17 .…”
unclassified